Suitability of coastal saline soils of Gopalapuram, Nellore for shrimp farming - Gupta, B P; Muralidhar, M; Joseph, K O; Krishnani, K K (Indian Journal of Fisheries, 2011)
Soil samples collected from various depths, at different sites of Gopalapuram farm area, Andhra Pradesh were analysed for their physico-chemical characteristics for the suitability of brackishwater aquaculture. The soils are poor in organic carbon (0.23 to 0.5 %). Average pH values ranged from 5.2 to 8.4. Low pH values are associated with higher values of iron and lower values of CaCOg. Textural class of soil varies from sandy loam to sandy clay loam. Sand/silt ratio values ranged from 4,0 to 10.3. Organic carbon, available nitrogen and phosphorus content of soil decreased with increasing depth of soil sampling. Iron content of soils was positively correlated with increasing depth and negatively correlated with pH and CaCOg content. Some important satistical correlations among soil characteristics were also worked out. The farm area was suitable for brackishwater aquaculture with suitable management of moderate limitation properties of the soils.